Ten Years after: Achievements and Challenges of the Euro-Mediterranean Economic and Financial Partnership - Juliane Brach (German Institute of Global and Area Studies (GIGA), 2006)
EU and twelve countries of the Middle East and North Africa (MENA) engaged in 1995 in the Euro-Mediterranean Partnership (EMP) in political, economic and cultural matters with the aim to foster cooperation, stability, and prosperity around the Mediterranean Basin. The Economic and Financial Partnership (EFP) plays a central role in the EMP design and implementation, which is centered on economic and trade integration as a starting point for and an anchor of socioeconomic development in the MENA region. Against this background, this paper reviews the situation in the MENA partner countries and the past performance of the EFP. It analyzes the association agreements, economic cooperation and financial assistance, discusses the major obstacles, and outlines the potential of the EFP to shape the European Neighborhood Policy. – – Seit 1995 engagieren sich die EU und zwölf Mittelmeerdrittländer in der Euro-Mediterranen Partnerschaft (EMP), die sicherheitspolitische, wirtschaftliche und kulturelle Themen umfasst, mit dem Ziel, Zusammenarbeit, Stabilität und Wohlstand im Mittelmeerraum zu fördern. Die Euro-Mediterrane Wirtschafts- und Finanzpartnerschaft (EFP) spielt eine wichtige Rolle in der Struktur und Umsetzung der EMP, die sich auf wirtschaftliche Integration und Handelsbeziehungen als Ausgangs- und Angelpunkte sozioökonomischer Entwicklung im Mittelmeerraum stützt. Vor diesem Hintergrund evaluiert der vorliegende Beitrag die Situation in den Mittelmeerdrittländern sowie die bisherigen Leistung der EFP und diskutiert Lösungsansätze für die wichtigsten Problemfelder. Darüber hinaus wird das Potential der EFP zur Gestaltung der Europäischen Nachbarschaftspolitik skizziert.
Keywords: O19; O53; F15; F5; 330; EU; Euro-Mediterranean partnership; Barcelona process; MENA; economic integration; socioeconomic development; Internationale Wirtschaftsbeziehungen; Internationale Zusammenarbeit; Mittelmeerraum; EU-Staaten